The highground: exploring landfill surface contouring for enhanced aesthetics in Southern California - Zhong, Yingyi (Kansas State University, 2020)
Daily waste production in the United States has steadily increased and follows population growth, especially in metropolitan areas and populated states. Since landfill permitting is typically a long and potentially controversial process, the trend is toward fewer but larger landfills. As a result, landfills near urban areas can be massive and are potentially seen by hundreds of thousands of people daily. Views of refuse being deposited is generally minimal, but as soil cover is incrementally added, the overall emerging landform is often visually incompatible with the surrounding topography. Many landfills tend to be geometrically shaped with angular faces, sharp corners, and mesa-like tops resulting in a flat ridgeline silhouette which can be recognized from great distances. Visual disruptions related to landfill operations can last for decades, and views after closure/restoration are permanent. This project and report explore to what degree landfills can be aesthetically contoured to more closely replicate contextual topography while maintaining high overall fill capacity. The study site is the Puente Hills landfill located in the urbanized Los Angeles basin. Additionally, 43 other landfills in Los Angeles County were inventoried to analyze geometric form and visual quality. From this group, three candidate landfills were selected for in-depth cross-sectional analysis. Extensive 3D modeling, using both manual and parametric methods, was then performed on the Puente Hills landfill to test various aesthetic “sculpting” scenarios. Corresponding volume capacity gains/losses were compared between enhanced landfill options and a landfill of standard configuration serving as the control. Findings attempt to show that enhanced landfill contouring is possible within acceptable engineering practices which could lead to easier landfill permitting by reducing visual impacts to the viewing public. This project and report also demonstrate how landscape architects can influence the aesthetic integrity of large landscapes that typically fall within the domain of civil engineers.
Keywords: Landfill; Terrain design; Contour; Earthwork; California; Aesthetics